The insurance services market in Ukraine: Problems and determinants of development in the conditions of digitization of the economy - Аnzhela Nikolaieva (Економічний форум, 2023)
The article examines the current state and features of the domestic insurance services market development, identifies and systematizes key problems in the field of insurance, indicates ways to solve them, and outlines the main determinants of the development of the insurance market in the context of digitalization of the economy. The purpose of the study is to identify and systematize the key problems of the insurance services market development in Ukraine, determine the ways to solve them and the determinants of the insurance market development in the context of digitalization of the economy. The study and systematization of literary sources and official reports of the NBU on the coverage of this issue testifies to the constant interest in this market segment among scientists and experts in the insurance field, and the need for further research to determine the main determinants of the activation of the insurance market development in the post-war period and in the context of further digitalization of the economy. The relevance of solving this scientific problem lies in the fact that recently there has been deterioration in the main indicators of the insurance market development in Ukraine, which, in our opinion, does not sufficiently fulfil its role in protecting and stabilizing the national economy. The study of the problem reflected in the article is carried out in the following logical sequence: analysis of the current state and development trends of the domestic insurance services market over the past six years; identifying the features of the activities of insurers during the war; systematization of key problems hindering their development with determination of ways to solve them; identification of priority digital technologies, the use of which can become a driver for the development of the domestic insurance market and will increase its competitiveness. The methodological tools of the study were a set of complementary methods: analysis and synthesis, causal analysis – to systematization of the reasons for restraining the insurance services market development in Ukraine, system-analytical, logical generalization – to develop ways to solve the identified problems and determine of the main determinants of its development. The object of the study is domestic insurance companies. The article presents the results of a causal analysis, which made it possible to determine a set of measures by the regulator and insurance companies aimed at overcoming the main problems in this industry. The results of a logical generalization are presented, which make it possible to determine the main digital technologies, the use of which can become a driver for the domestic insurance market development. The results of the study can be useful for Ukrainian insurance companies, which will allow them to increase their competitiveness in the market